Spermiogenesis and spermatozoal ultrastructure in Trichomycteridae (Teleostei: Ostariophysi: Siluriformes) - Spadella, Maria Angelica; Oliveira, Claudio [UNESP]; Quagio-Grassiotto, Irani [UNESP] (Wiley-Blackwell, 2010)
Spadella, M.A., Oliveira, C. and Quagio-Grassiotto, I. 2009. Spermiogenesis and spermatozoal ultrastructure in Trichomycteridae (Teleostei: Ostariophysi: Siluriformes). -Acta Zoologica (Stockholm) 91: 373-389.Siluriformes comprises the most diverse and widely distributed ostariophysan group, a fish assemblage that includes about three quarters of the freshwater fish of the world. In this study, the ultrastructural characterization of spermiogenesis and spermatozoa in specimens of Copionodontinae (the sister group to all other trichomycterids), Trichomycterinae (a derived trichomycterid group), and Ituglanis (a genus not assigned to any trichomycterid subfamily) is presented. The comparative analyses of the data show that trichomycterid species share six of seven analyzed spermiogenesis characters, reinforcing the monophyly of the group. Analyses of trichomycterid sperm ultrastructure showed that the species studied share the same character states for nine of seventeen characters analyzed. Copionodon orthiocarinatus and Ituglanis amazonicus each share more ultrastructural characters with species of Trichomycterus than with one another. Regarding the families of Loricarioidea, the species of Trichomycteridae share more characters of spermatogenesis, spermiogenesis, and sperm with representatives of the families Callichthyidae, Loricariidae, and Scoloplacidae than with Nematogenyidae, its hypothesized sister group. With the exception of the family Nematogenyidae, the character similarities observed reinforce the monophyly of the superfamily Loricarioidea.
Keywords: catfish; cysts of spermatids; spermatozoa; morphology; phylogeny